2019
DOI: 10.15446/caldasia.v41n2.67869
|View full text |Cite
|
Sign up to set email alerts
|

Comunidades de briófitos terrestres relacionados con factores climáticos y topográficos en un páramo del sur de Ecuador

Abstract: Los páramos presentan altos niveles de diversidad y endemismo de especies y son importantes en la regulación hidrológica. Sin embargo, es uno de los ecosistemas más amenazados debido a actividades agrícolas y ganaderas. Los briófitos son un importante componente en términos de diversidad, bio-masa y funcionamiento de estos ecosistemas. Estos organismos poiquilohídricos son muy sensibles a cambios en el microclima relacionados con la humedad, luz y temperatura. Se evaluaron los efectos de las variables climátic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
(34 reference statements)
0
2
0
2
Order By: Relevance
“…This indicates that water availability (e.g. rain, fog) is essential for the distribution of bryophyte species, as shown by many authors (Cavalier, 1996; Cavelier et al, 1996; Callaghan & Ashton, 2008; Benítez et al, 2019).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This indicates that water availability (e.g. rain, fog) is essential for the distribution of bryophyte species, as shown by many authors (Cavalier, 1996; Cavelier et al, 1996; Callaghan & Ashton, 2008; Benítez et al, 2019).…”
Section: Discussionmentioning
confidence: 61%
“…As a result, rainfall is expected to decrease towards higher elevations. Even though fog events are frequent, even during the dry season, at high elevations (Zotz et al, 2014) is essential for the distribution of bryophyte species, as shown by many authors (Cavalier, 1996;Cavelier et al, 1996;Callaghan & Ashton, 2008;Benítez et al, 2019).…”
Section: The Lack Of Undisturbed Ecosystems Outside Baru Volcanomentioning
confidence: 99%
“…Within the wide variety of species in the páramos, we can identify non-tracheophyte photoautotrophs (NVA), such as bryophytes, lichens, terrestrial algae, and cyanobacteria, that play key roles in the diversity and functioning of ecosystems, which is why deforestation and climate change (e.g., fire) cause negative effects [17]. Lichens and bryophytes are important components of non-tracheophyte photoautotrophs (NVA) due to their ability to retain water and improve infiltration in soils, which reduces erosion and provides organic matter to the soil [18][19][20]. These organisms have a high capacity to adapt to changes in environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Ecuador está entre uno de los 17 países en los cuales se concentra el 70% de la biodiversidad del planeta (Bravo, 2014); registra 1.690 aves (Comité Ecuatoriano de Registros Ornitológicos, 2017), 440 especies de www.concienciadigital.org mamíferos (Tirira, 2018) y posee la mayor diversidad de especies de reptiles y anfibios del mundo, calculadas en 1033 entre ambas clases (Bioweb, 2020). Esta diversidad se concentra en los bosques húmedos tropicales, en los subtrópicos orientales y occidentales, y en los bosques alto andinos correspondientes al páramo (Lozano, 2017;Benítez et al 2019). El páramo tiene una gradiente altitudinal que empieza desde los 3.000 m.s.n.m.…”
Section: Introductionunclassified
“…El páramo es un ecosistema vulnerable debido a la agricultura, ganadería, quemas, silvicultura y el cambio climático (Prieto-Torres et al, 2015;León-García y Laso 2019;Farley et al 2004;Beltrán et al 2009); la fauna silvestre como Pseudalopex culpaeus, Puma concolor, Mustela frenata está amenazada por la introducción de especies exóticas como ratas, perros y gatos ferales que compiten por territorialidad y alimentos (Schipper et al, 2008;Traveset, & Santamaría, 2004). Varios estudios reconocen que el páramo guarda diversidad biológica y endemismo (Balslev y Luetyn 1992; Luteyn 1999) sabiendo que las cadenas montañosas son barreras geográficas que limitan la distribución de las especies sobre todo de micromamíferos terrestres (Benítez et al 2019;Muñoz-Tobar y Catalino 2019). Los páramos también ofrecen servicios ecosistémicos como recolección, regulación y suministración de agua, muestra bellos paisajes para el ecoturismo, son esponjas naturales que sustentan de agua a grandes ciudades y retienen carbono orgánico (Ortiz y Mena, 2002;Buyataert et al, 2006;Castro, 2011).…”
Section: Introductionunclassified